Albie and the big race A small boy in a weird, wild world! - Cutbill, Andy (Thailand HarperCollins, 2010)
Meet Albie - a small boy in a weird, wild world. Albie is a six year old boy whose imagination turns his surroundings into wild fantasy and he sees peculiar creatures everywhere. Why does no one else notice them? It's a mystery to Albie. It seems like just another ordinary afternoon to Albie until he finds... penguins on a hostess trolley, zebras inside a grandfather clock and an elephant on a unicycle. Get your skates on, Albie! It's the Annual Smokin' Wheels Speed Convention!
F
b
b